Perlindungan Hukum Hak Kreditor dalam Sita Umum Kepailitan yang Bersinggungan dengan Sita Pidana Korupsi - Hendra Parulian; Iwan Erar Joesoef; Heru Sugiyono (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The intersection between general bankruptcy seizures and criminal seizures in corruption cases raises legal issues because it brings together private and public law regimes regarding the same object, namely the assets of the bankrupt debtor. This study aims to analyze the status of general bankruptcy seizures that conflict with criminal seizures for corruption, as well as the forms of legal protection for creditors’ rights based on Decision No. 16/Pdt.Sus-GLL/2017/PN. Niaga Jkt. The research method employed is normative legal research using a statutory approach, a case-based approach, and a conceptual approach, supported by primary, secondary, and tertiary legal sources. The research findings indicate that the panel of judges accepted the absolute jurisdiction exception and ruled that objections regarding the validity of criminal seizures fall within the jurisdiction of the criminal courts through the pre-trial mechanism. From the perspective of bankruptcy law, all assets of a debtor declared bankrupt are subject to general seizure for the benefit of all creditors, whereas criminal corruption law grants the authority to seize assets for the recovery of state losses. The conflict between these two regimes has the potential to hinder the liquidation of the bankrupt estate, delay the payment of creditors’ claims, and create legal uncertainty. Therefore, harmonization between bankruptcy law and criminal corruption law is necessary so that the protection of creditors’ rights and the interests of the state can be carried out in a balanced manner.